Factor Analysis of Cultural, Historical and Natural Tourism Determinants in Yogyakarta: Domestic Tourists Perspective - Anggi Rahajeng (Economic Journal of Emerging Markets, 2008)
This study is conducted to identify factors influencing the decision of tourists to visit Yogyakarta using factor analysis technique. Further, this study attempts to explore the perception of tourists on Yogyakarta tourism. Yogyakarta tourism has three main recreation attributes, i.e. cultural, historical, and natural attributes. Empirical results show that, overall, visitors are satisfied with the services provided in selected recreational sites. However there has been a lack in facilities and diversification of recreational activities. Therefore, some factors such as accommodation, satisfaction and recreation spot services become important aspects to attract visitors. Keywords: factor analysis technique, recreation’s attributes